Bridging the 'Know-Do' Gap Knowledge brokering to improve child wellbeing - Bammer, Gabriele (ANU Press, 2010)
Today's children are tomorrow's citizens. Good health and well-being in the early years are the foundations for well-adjusted and productive adult lives and a thriving society. But children are being let down in Australia and elsewhere by the lack of knowledge transfer between the worlds of research, policy and practice. Improving such transfer is the job of knowledge brokers - the various ways they can operate are explored in this book through case examples and the lessons learned from experienced proponents. The book concludes by posing three sets of ideas to shape the future of knowledge brokering.